ASPEK GRAMATIKAL DALAM WACANA POLITIK - Suwarna Suwarna (Universitas Muhammadiyah Surakarta, 2005)
The study is about grammatical aspects of the political discourse. Using technique of formal discourse analysis, especially focussing on cohesion, the grammatical aspects of political discourse show particular characteristics. Although in general they show reference, ellipsis, and conjunction, the discussion of the grammatical aspects is only limited on reference. The findings show that the use of reference in the political discourse can be classified into seven types: (1) reference showing cohesion which tends to be formal and standard; (2) reference having types of endophoric and exophoric, anaphoric, cataphoric, anaphoric and cataphoric, pronoun, demonstrative, and comparative pronoun reference consisting o0f temporal, locational, situational, equivalent, naming, historical; and reference having forms of lexical, phrasal, sentencial, paragraph, and discourse; (3) endophoric reference which is more productive than exophoric one; (4) anaphoric reference which is more productive than cataphoric one; (5) phrasal reference which is more productive than lexical, sentencial, paragraph, and discoursal ones; (6) cataphoric reference which tends to be phrasal and paragraph; and (7) discourse reference which is typically exophoric.Key words: grammatical aspect, cohesion, reference, political discourse, and korpus data